Sex differences in antisocial behaviour : (Cambridge University Press, 2001)
Why are females rarely antisocial and males antisocial so often? This is one of the key questions addressed in a fresh approach to sex differences in the causes, course and consequences of antisocial behavior. A multidisciplinary team of authors present all-new findings from the landmark Dunedin Longitudinal Study and also provide new insights into such topics as the importance of puberty, diagnostic issues in psychiatry, the problem of domestic violence and the intergenerational transmission of antisocial behavior.